Sojourn of the Sylvan Fringe: Receptivity to Mystery and Curricular Ruminations - Karrow, Douglas D.; Harvey, Sharon R. (Journal of the Canadian Association for Curriculum Studies, 2025)
This retrospective of an extended inquiry into the phenomenon of mystery addresses three questions: What is mystery?, revealing through hermeneutic phenomenology an unknown flower within a forest resuscitating metaphysics as physis, a definition of mystery founded on secrecy and incomprehensibility, and a conception of mystery as the enigma of the counterplay between the ontological movements of presencing and absencing (Caputo, 1986; Heidegger, 1927/1962); Why distain toward mystery?, where, through a literature review, a typology of senses of mystery problematizes this distain and expands awareness towards mystery. Openness to mystery begins through awareness, which heightens the senses and emotions, kindling poetic knowledge, a foundational mode of being. Mystery also serves as a measure for our lives, through our consonant comportments and conceptions. The comportment of humility, among others, is highlighted as nurturing mystery; and How may receptivity toward mystery inform curriculum theory?, where the consideration of “what should be learned” (Petrina, 2004), supports a conception of education in which future generations recognize metaphysics as presence, while awakening to metaphysics as physis.